THE MEANING OF AUTHORITY RELATION OF CENTRAL GOVERNMENT AND LOCAL GOVERNMENT IN THE LAND SECTOR ACCORDING TO THE 1945 CONSTITUTION OF THE REPUBLIC OF INDONESIA - Zaman, Nurus (Yustisia, 2017)
In this study, there are two (2) issues that were examined. First, how the Central Government and Local Government gained authority in the land sector. Second, how the meaning of the relationship of authority of the Central Government and Local Government in the area of land according to the 1945 Constitution, This study uses normative legal research. The results of research are: First, the authority of the Central Government in the land sector is the inherent nature of authority, because as the sole power in a unitary state. In the development of central government authority derived from attributive authority and Local Government authorities in the land sector sourced from attributive authority and discretionary. Second, the meaning of the relationship of authority between the central government and the regional government in the land sector as: (a) the relationship of subordination; (B) the relationship of supervision; and (c) the relationship of responsibility in achieving the objectives of the State.